2008
DOI: 10.1073/pnas.0808589105
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA polymerase η activity and translocation is regulated by phosphorylation

Abstract: Human DNA polymerase (pol ) can replicate across UV-induced pyrimidine dimers, and defects in the gene encoding pol result in a syndrome called xeroderma pigmentosum variant (XP-V). XP-V patients are prone to the development of cancer in sun-exposed areas, and cells derived from XP-V patients demonstrate increased sensitivity to UV radiation and a higher mutation rate compared with wild-type cells. pol has been shown to replicate across a wide spectrum of DNA lesions introduced by environmental or chemotherape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 50 publications
3
51
1
1
Order By: Relevance
“…Embryos from WT and pol η −/− mice were harvested on day 13.5 for the generation of MEF cells (54). The established pol η −/− MEF cells were transfected with either WT human pol η (hPol η WT) or the R61F mutant form of human pol η (hPol η R61F) (55). The protein expression level of pol η was examined by Western blot analysis with anti-human or anti-mouse pol η antibodies from Biorbyt.…”
Section: Methodsmentioning
confidence: 99%
“…Embryos from WT and pol η −/− mice were harvested on day 13.5 for the generation of MEF cells (54). The established pol η −/− MEF cells were transfected with either WT human pol η (hPol η WT) or the R61F mutant form of human pol η (hPol η R61F) (55). The protein expression level of pol η was examined by Western blot analysis with anti-human or anti-mouse pol η antibodies from Biorbyt.…”
Section: Methodsmentioning
confidence: 99%
“…After UV irradiation, the monoubiquitination of pol is down-regulated to expose the PCNA-interacting surface, thereby stimulating pol 's interaction with PCNA and facilitating TLS (17). In addition, previous studies showed that pol can be phosphorylated at serine 587, threonine 617, and serine 601 (Ser 601 ), which are required for normal survival and efficient recovery from UV damage (18,19). It is therefore important to identify other possible posttranslational modification(s) of hu-man pol for further understanding the regulatory mechanisms of this important TLS polymerase.…”
mentioning
confidence: 99%
“…Platinum compounds react with DNA and lead to DNA lesions, including intrastrand crosslinks (Pt-d[CpG], Pt-d [ApG] and Pt-d [GpNgG]), interstrand crosslinks and single nucleotide damage involving guanine [43] . Hence, TLS that allows bypass of the intrastrand crosslinks and constitutes a critical initial step in interstrand crosslink repair [44] is advantageous to tumor cells' survival [45][46][47][48] . These crosslink bypasses can result in resistance against platinum-based chemotherapy [47,49] .…”
Section: Discussionmentioning
confidence: 99%